FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PERUSAHAAN TERDAFTAR DI BURSA EFEK INDONESIA - Elisabeth Tri Aryanti Istimawani (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study is to examine the factors that influence dividend policy. The factors are company growth, free cash flow, profitability, investment opportunity set, liquidity, firm size, leverage, company life cycle, asset turnover, and institutional ownership. Population of this research are all of non financial companies listed in Indonesia Stock Exchange from 2010 to 2015. The samples are collected using purposive sampling method and there are 40 companies meet those criteria for samples. This research uses multiple regression method for data analysis. The result of this research indicates that free cash flow, liquidity, firm size, company life cycle, and asset turnover have influence to dividend policy. While company growth, profitability, investment opportunity set, leverage, and institutional ownership do not have influence to dividend policy.